Tisztelet – közömbösség – helytelenítés? : A nemzetszocialista államjog az osztrák jogi diskurzusban - Staudigl-Ciechowicz, Kamila (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Based on the legal developments and leading constitutional experts in the late 19th century, the article shows how (Viennese) law professors dealt with questions of German law in academia and studies. Against the backdrop of the Austrian authoritarian era from 1933 to 1938, it examines how politically opposed university lecturers were dealt with in Austria and raises the question of whether and how critical opinions on Austrian and German state law were expressed by law professors. In this context, some leading legal journals from the years 1933 to 1938 are analysed. Initially, Austrian legal scholars concentrated primarily on developments in their own constitutional law and legal practice. It is striking that under Austrofascism, Austrian studies on German law declined and critical analyses of National Socialist law were very rare.